Prescription analysis and drug utilization pattern in a tertiary care teaching hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
BackgroundPeriodic prescription analysis is one of the methods to assess drug utilization and rationality of prescribing. It should be regularly conducted to improve the quality of prescription and curb the menace of irrational prescribing which has become a worldwide problem.ObjectivesTo analyze the rationality status of prescriptions and drug utilization pattern in inpatients admitted in a tertiary care hospital.Materials and MethodsThe present observational retrospective study was carried out in inpatients of Medicine, Surgery, Gynaecology, Pediatrics, Skin, Orthopaedics and Psychiatric departments of our tertiary care hospital over a period of three months during which data of 200 patients were collected. The age, sex and diagnosis of the patients were noted. The rationality of prescriptions was evaluated using WHO core indicators of drug utilization.ResultsTwo hundred prescriptions were analysed in which 1036 drugs were prescribed. Mean number of drugs per prescription was 5.18. In our study, 75.97% drugs were prescribed by generic names and drugs from  EDL were 75.48%. Dosage forms used were mostly oral (60.71%). Infectious diseases were the most common illnesses (19.5%) followed by diseases of respiratory system. The most common drug groups prescribed were antimicrobials, analgesics & anti-inflammatory drugs, GIT , multivitamins and minerals. The incidence of poly-pharmacy was also common with maximum number of prescriptions (36.5%) having five drugs per prescription.ConclusionPrescription analysis is an important measure to improve the quality of care afforded by the hospitals. Establishment and implementation of appropriate clinical guidelines, use of essential medicines list, continuing medical education and regular update to the clinicians will help in implementing the principles of rational pharmacotherapeutics.